1992
DOI: 10.1038/icb.1992.18
|View full text |Cite
|
Sign up to set email alerts
|

Defining the nucleic acid substrate for somatic hypermutation

Abstract: Recent reports have more precisely defined the distribution of somatic mutations around rearranged mouse V-D-J genes. The 5' boundary of mutation is most likely in the region of the transcription start site (cap) and/or the promoter (P), implying that transcription may be a prerequisite for mutations to be generated. As more than 95% of somatic mutations lie downstream of the cap site, the transcription unit itself is implicated as the target of the mutational machinery. For heavy chain genes, the 3' boundary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 0 publications
4
30
0
Order By: Relevance
“…Therefore V(D)J transgenes with a reporter tRNA in the J-C intron upstream of E i /MAR should not mutate in the V(D)J target region because cDNA synthesis will be prevented from proceeding through the tRNA sequence (¢gure 2a). The data published by Umar et al (1991) and Umar & Gearhart (1995) support this prediction (also see Steele et al (1992Steele et al ( , 1997 for further explanation and analyses of these data).…”
Section: Dynamics Of the Rt Model Exemplified By Data Outside The Ambsupporting
confidence: 71%
See 1 more Smart Citation
“…Therefore V(D)J transgenes with a reporter tRNA in the J-C intron upstream of E i /MAR should not mutate in the V(D)J target region because cDNA synthesis will be prevented from proceeding through the tRNA sequence (¢gure 2a). The data published by Umar et al (1991) and Umar & Gearhart (1995) support this prediction (also see Steele et al (1992Steele et al ( , 1997 for further explanation and analyses of these data).…”
Section: Dynamics Of the Rt Model Exemplified By Data Outside The Ambsupporting
confidence: 71%
“…Alternatives suggested at the time were (i) premature termination of RNA synthesis; (ii) cleavage of pre-mRNA, coupled to hairpin loop RT priming; or (iii) speci¢c primer binding sites by analogy with tRNA primers in retroviral reverse transcription (Steele & Pollard 1987). Later, multiple RT-priming sites in the J-C intron were invoked (Steele et al 1992) to explain the asymmetrical distribution of somatic point mutations (Both et al 1990;Lebecque & Gearhart 1990;Weber et al 1991;Steele et al 1992;Rothen£uh et al 1993) (¢gure 1b). More recently, multiple priming sites and a number of alternative RT-priming mechanisms have also been advanced to attempt to explain both the asymmetry of the distribution and focusing to the particular V(D)J rearrangement undergoing hypermutation (discussed in Steele et al 1997; cf.…”
Section: Historymentioning
confidence: 99%
“…A composite graph of a limited data set showing the distribution in mutation frequencies across a VDJH.~ gene suggested that the distribution of mutations around VDJ genes may be asymmetrical and that the mutation frequency 5' of the cap site was at least an order of magnitude lower than that 3' of the cap site (reviewed in [17]). An important outcome of this data review was that more sequences of 5' flanking regions was obviously required.…”
Section: Discussionmentioning
confidence: 98%
“…An earlier review of available data suggested that the distribution of somatic mutations around rearranged V regions may be positively skewed, with a single mode centred on the V(D)J gene and a long tail extending into the J-C intron [17], however it was pointed out that a larger data set was required for a more conclusive analysis. Therefore, to determine accurately the nature of the underlying frequen-cy distribution and 5' boundary for somatic hypermutation we have now sequenced an additional 12 somatically mutated, rearranged VH regions and their 5' flanking regions to a point approximately 520 bp upstream of the transcription start (cap) site.…”
Section: Introductionmentioning
confidence: 97%
“…The RT model still provides the best explanation for the gradual decline as explicitly stated by Steele, Rothenfluh and Both over a decade ago. 12 In this model, a family of errorfilled cDNA (produced by the RT activity of pol η ), initiated at various evenly spaced priming sites over the V(D)J and J-C intron of the pre-mRNA template, replace the original TS DNA in the populations of B cells assayed for SHM. Synthesis of cDNA on the pre-mRNA template should continue to the end of the template unless blocked by RNA structure orat the 5 ′ boundary.…”
Section: The Distribution Of Mutations In Rearranged Igv Genesmentioning
confidence: 99%